Examining the relationship between living conditions, work environment and intent to stay among nurses in current posts in rural areas of Odisha state, India - Behera, Manas Ranjan; Behera, Deepanjali; Prutipinyo, Chardsumon (Bangladesh Journal of Medical Science, 2020)
Objectives : The scarcity of nursing workforce in rural and underserved areas are key challenges for healthcare systems across the countries. Such inequities have not only impede quality care but also an impact to population health outcomes especially in developing countries. An understanding about nurses’ retention and attrition are crucial to inform policy and decision makers for improved rural retention among nursing workforce. The aim of the study was to examine the relationship between living conditions, work environment and intent to stay in current posts of work; and the associated factors influencing intent to stay in current posts of work among nurses in rural areas of Odisha state, India. Methods : A cross sectional survey was conducted among 232 nurses from October 2016 to February 2017. Multistage sampling technique was used to select the study subjects from rural hospitals. Data were collected using structured self-administered questionnaires. Descriptive statistics were computed to summarize the basic characteristics of study sample. Logistic regression model was fitted and odds ratio with 95% of confidence interval was calculated to identify associated factors Results: The proportion of a nurse’s intent to stay and continue working in rural areas for next 3 years was 73.7%. There was a positive correlation between intention to stay with the living conditions and work environment. Logistic regression shown that age (OR=0.95, 95% CI = 0.89 - 0.98, P = 0.047), living conditions (OR = 1.13, 95% CI = 1.04 - 1.22, P=0.009) and work environment (OR = 1.07, 95% CI = 1.01 – 1.14, P = 0.015) were the significant predictors that are associated with intent to stay in rural areas among the nursing profession. Conclusion - Improving living conditions and creating a culture of supportive work environment among the nursing community in rural areas can create increased retention in the workforce. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.527-536